Acting for America : Movie Stars of the 1980s - Eberwein, Robert T., 1940- (Book collections on Project MUSE., 2010)
Acting for America focuses on the way film icons have engaged in and defined some major issues of cultural and social concern to America during the 1980s. Scholars employing a variety of useful approaches explore how these movie stars' films speak to an increased audience awareness of advances in feminism, new ideas about masculinity, and the complex political atmosphere in the Age of Reagan. The essays demonstrate the range of these stars' contributions to such conversations in a variety of films, including blockbusters and major genres.